Oxidative damage in the liver and brain of the rats exposed to frequency-dependent radiofrequency electromagnetic exposure: biochemical and histopathological evidence. (4th May 2021) - Sharma, Anjali; Shrivastava, Sadhana; Shukla, Sangeeta
Abstract: The study aimed to discover a link between the liver and brain's functional status due to frequency dependent-radiofrequency electromagnetic radiation (RF-EMR). Forty Wistar rats were randomly classified as control (sham-exposed) and EMR exposed groups. Animals were exposed to 900, 1800, and 2100 MHz with the specific absorption rate (SAR) 0.434 (W/Kg), 0.433 (W/Kg), and 0.453 (W/Kg) respectively. Animal exposure was limited at 1 h/day, 5 days/week for 1 month with a restricted power density (900 MHz- 11.638 µW/m 2, 1800- 11.438 µW/m 2 and 2100 MHz frequency- 8.237 µW/m 2 ). Exposure at various frequencies showed a frequency-dependent change in the body weight and hematologic parameters (RBCs, WBCs, platelets, hemoglobin, and hematocrit) as compared with the control group ( p  ≤ 0.01) ( p  ≤ 0.001). A significant elevation in serum transaminases and bilirubin, urea, uric acid, and creatinine was noted, whereas albumin significantly decreased after EMR exposure ( p  ≤ 0.01) ( p  ≤ 0.001). The blood glucose, lipid peroxidation, triglycerides, and cholesterol were elevated while adenosine triphosphatases, acetylcholinesterase, and tissue antioxidants such as glutathione, superoxide dismutase, catalase, glutathione reductase, glutathione Peroxidase, glutathione - S - transferase, and glucose-6-phosphate dehydrogenases were decreased significantly ( p  ≤ 0.001). Histopathological observations of the liver showed centrilobular mononuclear cell infiltration and swelling in sinusoidal spaces, while in the brain degenerated pyramidal and Purkinje neurons were seen. Furthermore, Substantial evidence was found that the brain is more susceptible to oxidative mutilation compare to the liver of exposed animals. In conclusion, RF-EMR exposure showed oxidative damage to the liver, increasing the incidence of brain damage in a frequency-dependent manner. Highlights: EMR exposure showed frequency-dependent toxicity. Alterations in blood profile and modifications in the serological markers. Increasing lipid peroxidation indicating membrane damage. Inhibition of acetylcholinesterase activity affecting cholinergic neurotransmission. EMR exposure resulted in the loss of cellular energy and production of excess amounts of ROS thereby altering several antioxidant enzymes. Histopathological evidence of severe degenerative changes in the liver and brain.